Def6 Restrains Osteoclastogenesis and Inflammatory Bone Resorption - Binder, Nikolaus; Miller, Christine; Yoshida, Masaki; Inoue, Kazuki; Nakano, Shinichi; Hu, Xiaoyu; Ivashkiv, Lionel B.; Schett, Georg; Pernis, Alessandra; Goldring, Steven R.; Ross, F. Patrick; Zhao, Baohong (Journal of Immunology, 2017)
Inflammatory bone resorption mediated by osteoclasts is a major cause of morbidity and disability in many inflammatory disorders, including rheumatoid arthritis (RA). The mechanisms that regulate osteoclastogenesis and bone resorption in inflammatory settings are complex and have not been well elucidated. In this study, we identify the immunoregulator differentially expressed in FDCP 6 homolog (Def6) as a novel inhibitor of osteoclastogenesis in physiological and inflammatory conditions. Def6 deficiency in Def6(-/-) mice enhanced the sensitivity of osteoclast precursors to the physiological osteoclastogenic inducer receptor activator for NF-?B ligand, and Def6(-/-) osteoclasts formed actin rings. Furthermore, Def6 deficiency markedly increased TNF-?-induced osteoclastogenesis in vitro and in vivo and enhanced bone resorption in an inflammatory osteolysis mouse model. TNF-? serum levels correlated negatively with Def6 expression levels in osteoclast precursors obtained from RA patients, and the osteoclastogenic capacity of the osteoclast precursors was significantly inversely correlated with their Def6 expression levels, indicating that Def6 functions as an inhibitor of excessive osteoclast formation and bone destruction in RA. Mechanistically, Def6 suppressed osteoclastogenesis and the expression of key osteoclastogenic factors NFATc1, B lymphocyte-induced maturation protein-1, and c-Fos by regulating an endogenous IFN-?-mediated autocrine feedback loop. The Def6-dependent pathway may represent a novel therapeutic target to prevent pathological bone destruction.
EVALuna2:13411